Policies and Practices of Health Promotion in Nepal - Karki, Binod Kumar (KMC Research Journal, 2018)
Health promotion is the process of enabling people to increase and improve their health. Health Promotion has globally emerged as a separate stream of public health but in Nepal it is still a relatively new concept. There are challenges related to research in the field of health promotion. Health promotion requires policy makers across all government departments to make health a central line of government policy. The aims of this study is to discover key policies and strategies of health promotion in Nepal and to identify the different activities and practices carried out by them. This study is based on review of the national health policies that were published in different period of time. The paper argues that health promotion requires policy makers across all government bodies to make health a central line of government policy since health policy is one of the most important aspects of the livelihood development of a country.